Historico-genetic Theory of Culture: On the Processual Logic of Cultural Change - Dux, Günter (transcript, 2014)
The book focuses on the modern understanding of human life-forms as constructs that followed an evolutionary history. The author thus finds science confronted with two questions: firstly, how the transgression of the virtual threshold between natural and cultural history was possible, secondly, how the socio-cultural constructs were able to develop in the course of history the way they did. The discussion concentrates on the problem of determining a processual logic in the development of societal structures as well as in the development of cognition. The focus of attention is the historico-genetic reconstruction of cognition.The book was originally published in German as »Historisch-genetische Theorie der Kultur« (Weilerswist 2000: Velbrück).